Pengaruh Aliran Filsafat terhadap Pemikiran Neo-Sufisme di Nusantara - Trisnani, Asif; Naya, Arsya; Ainurrohmatillah, Putri (Proceedings of International Conference on Muslim Society and Thought, 2024)
Abstract: The emergence of Neo-Sufism was influenced by the development of civilization in medieval Islam which had experienced a decline from spiritual traditions in the realm of Islamic thought. Neo-Sufism originated from the influence of philosophical thought in order to reconcile between religion and social understanding due to the crisis of the phenomenon of modernization in religious communities. This is related to the concept of philosophy which is considered less logical and contrary to the teachings of Islam so that it experiences a rejection reaction to the teachings that unite the essence of man with God. This school of Philosophy prioritizes the ratio above the authentic proof or revelation, so that the conflict of deviation will be greater because of the opposite in the Qur'an and Sunnah. This study aims to examine the influence of philosophical schools of Thought on Neo-Sufism and criticize the concept of philosophical schools in the archipelago. This method uses qualitative methods with libelarisis-based comparative analysis method. The results of this study revealed that the thought of Neo-Sufism is influenced by the flow of philosophy that led to the renewal of Sufism in the Nusantara.